The effect of playing exercises in accordance with the intense small groups on the field in developing offensive skills for basketball juniors - IRHAYYIM, THAMER KADHIM; MOHAMMED, ABD ALI JAAFAR; ALWAN, HASSAN FARHAN (International Journal of Psychosocial Rehabilitation, 2020)
AbstractThe importance of research in developing effective, interesting and targeted exercises suitable for age groups, especially juniors, works to raise the level of offensive skills, in addition to that we will build a basic base in the formations of advanced teams from Iraqi teams that help advance the basketball in our country.The main objectives of the research were:• Prepare the practices of playing according to the intense small groups on the field in the development of the offensive skills of the basketball to juniors.Most important conclusions: - Training in the small, intense groups on the field has been successful in developing the offensive skills of the basketball to juniors.The most important recommendations: - adopting the practice of playing according to the small groups intensive inside the stadium as it has achieved success in the development of the offensive skills of the basketball to juniors.